Three-color osmanthus heterophyllus potting cultivation method - DAI QIN; XU MENG; WANG DONGMEI (2018)
The invention provides a three-color osmanthus heterophyllus potting cultivation method, and relates to the technical field of plant potting cultivation. The potting cultivation method includes the steps of potting container selection, seedling cultivation pot filling and seedling cultivation post-management. A three-color osmanthus heterophyllus obtained by the three-color osmanthus heterophylluspotting cultivation method is rare in disease and pest injury, easy to plant and manage, high in survival rate and can realize foliage and perfume smelling, and has more market potential and development space as compared with a shrub. 本发明提供种三色柊树的盆栽栽培方法，涉及植物盆栽栽培技术领域。本发明盆栽栽培方法为：选择盆栽容器、幼苗栽种填盆、幼苗栽种后管理。本发明三色柊树的盆栽栽培方法获得的三色柊树的病虫害极少，容易栽植，成活率高，容易管理，可以观叶，闻香，与灌木相比更具有市场潜力和发展空间。